On the existence of solutions of some non-linear functional integral equations in Banach algebra with applications. Issue 1 (1st January 2020) - Deep, Amar, Deepmala; Tunç, Cemil
Abstract: In this article, we establish some results for the existence of solution of nonlinear functional integral equations by using Darbo's fixed point theorem in Banach algebra. As an application, we discuss some examples of nonlinear functional integral equations and existence of solutions.